The Semiotics of a Manggarai Wedding: Language and Meaning - Yustiana Maria Ndia; Cheng Ching Yee; Frederic Carral; Saraswathy Selvarajan; Junyawan Suwannarat (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the forms, meanings, and semiotic functions of language in the traditional wedding discourse of the Flores culture in West Manggarai Regency, East Nusa Tenggara, Indonesia. Methodology: The research uses a qualitative descriptive approach. Data were collected through structured interviews and participatory observation, supported by documentation such as photos and field notes. Data analysis was conducted using qualitative descriptive techniques and the referential equivalence method (metode padan referensial). Main Findings: The study identified unique semiotic forms in both linguistic units (words, phrases, sentences, discourse) and non-linguistic elements (symbols, objects, participants) throughout the wedding stages. These elements carry specific cultural meanings and functions, reinforcing social bonds, cultural identity, and communication within the Manggarai Barat community. Novelty/Originality of this study: This research provides a semiotic analysis of Manggarai Barat wedding rituals using Halliday’s sociosemiotic framework, which has not been extensively applied in previous studies on Flores culture. It contributes to the preservation and linguistic documentation of local oral traditions and enriches the study of language-culture correlations in Indonesia.